Genetic deletion of HVEM in a leukemia B cell line promotes a preferential increase of PD-1- stem cell-like T cells over PD-1+ T cells curbing tumor progression - del Rio, Maria-Luisa; de Juan, Carla Yago-Diez; Roncador, Giovanna; Caleiras, Eduardo; Álvarez-Esteban, Ramón; Pérez-Simón, José Antonio; Rodriguez-Barbosa, Jose-Ignacio (Frontiers in Immunology, 2023)
Introduction A high frequency of mutations affecting the gene encoding Herpes Virus Entry Mediator (HVEM, TNFRSF14) is a common clinical finding in a wide variety of human tumors, including those of hematological origin. Methods We have addressed how HVEM expression on A20 leukemia cells influences tumor survival and its involvement in the modulation of the anti-tumor immune responses in a parental into F1 mouse tumor model of hybrid resistance by knocking-out HVEM expression. HVEM WT or HVEM KO leukemia cells were then injected intravenously into semiallogeneic F1 recipients and the extent of tumor dissemination was evaluated. Results The loss of HVEM expression on A20 leukemia cells led to a significant increase of lymphoid and myeloid tumor cell infiltration curbing tumor progression. NK cells and to a lesser extent NKT cells and monocytes were the predominant innate populations contributing to the global increase of immune infiltrates in HVEM KO tumors compared to that present in HVEM KO tumors. In the overall increase of the adaptive T cell immune infiltrates, the stem cell-like PD-1- T cells progenitors and the effector T cell populations derived from them were more prominently present than terminally differentiated PD-1+ T cells. Conclusions These results suggest that the PD-1- T cell subpopulation is likely to be a more relevant contributor to tumor rejection than the PD-1+ T cell subpopulation. These findings highlight the role of co-inhibitory signals delivered by HVEM upon engagement of BTLA on T cells and NK cells, placing HVEM/BTLA interaction in the spotlight as a novel immune checkpoint for the reinforcement of the anti-tumor responses in malignancies of hematopoietic origin.